Current state of cutinases in addressing the issue of single-use plastic degradation - Arrieta-Fonseca, Marcel (2024)
The widespread consumption of single-use plastics has caused an environmental crisis due to their overaccumulation in ecosystems. This article explores the current status of cutinases, one of the main types of enzymes with the potential to degrade single-use plastics. Cutinases (EC 3.1.1.74) are serine hydrolases of the group of α/β hydrolases capable of catalyzing reactions that degrade polymers, mainly polyethylene terephthalate (PET) and polybutylene adipateco-terephthalate (PBAT), and are produced by bacteria, filamentous fungi and yeasts. Each enzyme has different characteristics depending on its microorganism of origin, with those of fungi and yeast being more similar to each other than those of bacteria. Biotechnological tools, such as synthetic biology, have proven to be innovative strategies capable of improving the efficiency and stability of cutinases in the degradation of plastics, capable of offering a possible sustainable solution to the environmental crisis caused by these materials.